Diagenesis Analysis of Padengo Limestone Area, Gorontalo Regency Based on Petrographic Method - Fikri Boften; Aang Panji Permana; Muhammmad Kasim (Journal of Applied Geospatial Information, 2023)
Carbonate rocks are rocks composed of carbonate minerals that are chemically formed in the form of solutions, and there are organisms involved in their formation. The limestone found around Lake Limboto is very interesting, because the water in the lake is freshwater while the limestone is characteristic of a marine environment. Diagenesis is a natural process in sedimentary rocks that occurs from the initial deposition until it reaches the limit of metamorphism will be formed. The research area is located in Padengo Village, West Limboto Subdistrict, Gorontalo Regency with a research area of 7.72 Km2. This research aims to analyze the diagenesis of limestone in the Padengo area of Gorontalo Regency using the petrographic method. The methods used are field geological survey and petrographic analysis. The results showed that the geology of the Padengo area is composed of a wackestone limestone facies unit, a crystalline limestone facies unit, and an alluvial sediment unit. The diagenesis type of the study area consists of neomorphism, micritization, dissolution, cementation, and dolomitization. From the type of diagenesis, it can be determined that the limestone diagenesis environment of the study area starts from the marine phreatic zone, then the burial zone, and ends at the meteoric vadose zone.